AMIL COMPETENCE AND ZAKAT MANAGEMENT EFFECTIVENESS: EVIDENCE FROM ZAKAT INSTITUTIONS - Nunung Nurhayati; Diamonalisa; Kania Nurcholisah; Nurleli; Helliana; Ayunazwa (UPT Publikasi Ilmiah UNISBA, 2025)
This study aims to analyse the influence of zakat administrators’ competencies on the effectiveness of zakat fund management at Zakat Management Institutions (LAZ) in the city of Bandung, using a quantitative approach and survey methods, as well as data collected via questionnaires. Using purposive sampling, a sample of 45 respondents—who are zakat administrators at LAZs in the city of Bandung—was obtained. Linear regression analysis was used to test the relationship between zakat administrators’ competencies—which include knowledge of Islamic law, managerial skills, and social skills—and the effectiveness of zakat distribution and collection. The results indicate that zakat administrators’ competencies have a positive and significant impact on the effectiveness of zakat fund management, particularly in enhancing donors’ trust and empowering recipients. These findings have practical implications for LAZs to standardise training and certification for zakat administrators. Socially, enhancing the competencies of zakat administrators contributes to strengthening the role of zakat as a tool for social welfare. This study emphasises the importance of investing in the development of zakat human resources as a strategic value-add in professional and impactful zakat management.